EFFECTIVENESS OF THE DISTRIBUTION OF 3 KG LIQUEFIED PETROLEUM GAS (LPG) CYLINDERS TARGETED ACCORDING TO PRESIDENTIAL REGULATION NUMBER 38 OF 2019 ON THE PROVISION, DISTRIBUTION, AND PRICE DETERMINATION OF LIQUEFIED PETROLEUM GAS FOR FISHING VESSELS FOR TARGETTED FISHERMAN AND WATER PUMP MACHINES FOR TARGETTED FARMES - Ardiansyah, Ata; Rahmatiar, Yuniar; Abas, Muhamad (Universitas Islam Negeri Ar-Raniry, 2024)
The delivery pf 3 kg LPG fuel has a great effect on the survival of the community, but the distribution is not in accordance with the standards, it can cause problems such as misuse of distribution, triggering criminal acts and can cause a scarcity of 3 kg LPG gas supply. The problem is how effective is the distribution of 3kg cylinder liquified petroleum gas (LPG) on target based on Presidential Regulation Number 38 of 2019 concerning the Supply, Distribution, and Pricing of Liquefied Petroleum Gas for Fishing Vessels for Target Fishermen and Water Pump Machines for Target Farmers and How the Challenges in Distributing 3kg Cylinder Liquified Petroleum Gas (LPG) Cylinders Are Right on Target. Qualitative Research Method using the Normative Juridical approach method. The results of the research are based on the Presidential Regulation of the Republic of Indonesia Number 38 of 2019 concerning the Supply, Allocation, and the rates for Liquefied Petroleum Gas for fishing boats aimed at fisherman and water pump machinery designed for farmers, it’s stated that the provision and distribution of LPG for target fishermen’s fishing boats and target farmers water pumping equipment use 3 Kg LPG Cylinders for households and micro businesses. The challenge in distributing 3kg LPG Cylinders on Target is that the Government of Indonesia continues to strive to transform LPG subsidy policies that are more targeted. One of the steps is to change the LPG subsidy scheme from originally commodity-based to individual-based. However, in the implementation of this transformation plan, there are various challenges and problems that need to be overcome, including 1) Beneficiary Data; 2) Implementation in the Field; 3) Enforcement of Subsidy Distribution Rules; 4) Effectiveness of Monitoring and Supervision; 5) Impact on the Poor and Vulnerable